Low odor crosslinking masterbatch for polyolefins and method of making and use thereof

CN122404838BActive Publication Date: 2026-10-09SHANDONG PROVINCE BOYUAN CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202610893992.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-09
Estimated Expiration
2046-06-22

AI Technical Summary

Technical Problem

然而,此类传统防焦烧剂的作用机理是不可逆地消耗体系中的自由基,这会导致大量有效自由基被浪费,从而降低最终制品的交联密度

Benefits of technology

(1)本发明利用特定粉体表面接枝的异氰酸酯基团,在高温硫化阶段与气味分子的羟基发生亲核加成反应,构建了化学性质相对稳定的氨基甲酸酯共价键。相较于传统的物理吸附机制,这种共价键合方式在80℃热老化30天及乙醇萃取处理后的气味等级仍能维持在VDA2702.0级以下,表明其在典型使用条件下的抗脱附能力优于物理吸附。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122404838B_ABST
    Figure CN122404838B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of polymer material processing aids, in particular to a low-odor crosslinking master batch for polyolefins and a preparation method and application thereof. The crosslinking master batch contains, in parts by weight, 30-50 parts of a carrier resin, 20-40 parts of an organic peroxide crosslinking agent, 10-20 parts of a multifunctional crosslinking aid, 0.1-2.0 parts of a temperature-responsive anti-scorching agent and 10-20 parts of a covalent odor-locking powder. The temperature-responsive anti-scorching agent is a nitrogen-oxygen free radical compound, and the covalent odor-locking powder is inorganic silica powder with active isocyanate groups grafted on the surface. The temperature-responsive anti-scorching agent can capture free radicals at low temperatures and release free radicals at high temperatures, so that the processing safety and crosslinking efficiency are considered to some extent, and the odor revival problem caused by the physical adsorption mechanism is relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer processing aids, specifically to low-odor crosslinking masterbatch for polyolefins, its preparation method, and its application. Background Technology

[0002] Crosslinked foam materials of polyolefins (such as ethylene-vinyl acetate copolymers, polyethylene, and polyolefin elastomers) are widely used in footwear, automotive interiors, and building decoration due to their excellent mechanical strength and resilience. Currently, organic peroxides (such as dicumyl peroxide and bis(tert-butylperoxyisopropyl)benzene) are commonly used in industry as crosslinking initiators to achieve crosslinking of polyolefin macromolecular chains through high-temperature initiation of free radical reactions.

[0003] However, existing crosslinking technologies face dual challenges in terms of processing safety and product odor control.

[0004] First, organic peroxides produce small-molecule byproducts with pungent odors, such as alcohols (e.g., tert-butanol, dimethylbenzyl alcohol) and ketones (e.g., acetophenone), during high-temperature pyrolysis. To reduce the odor of finished products, existing technologies often employ the addition of physical adsorbents. For example, Chinese patent application CN118085457A, published on May 28, 2024, discloses a low-odor thermoplastic elastomer that adsorbs small-molecule volatiles by adding deodorizing agents such as porous carbon and metal-organic frameworks (MOFs). Chinese patent application CN103497429A, published on January 8, 2014, also discloses a low-odor TPV formed by secondary coating with an ABS substrate, using porous carriers such as zeolite and molecular sieves as deodorizing agents. However, this type of physical adsorption mainly relies on van der Waals forces, and its binding strength is relatively limited. During subsequent use in high-temperature environments (such as above 80°C) or long-term storage, some adsorbed odor molecules may desorb, leading to an "odor recovery" phenomenon, which poses a challenge to meeting the long-term low-odor requirements of high-end fields such as automotive interiors.

[0005] Secondly, there is an inherent contradiction between crosslinking efficiency and processing safety. During the mixing stage, to prevent peroxides from prematurely decomposing due to shear heat (i.e., "scorching"), hindered phenolic antioxidants are typically added as anti-scorching agents. For example, Chinese patent application CN105153621A, published on December 16, 2015, discloses a silane crosslinking composition for preventing pre-crosslinking and rapid curing, which uses long-chain alkyl silanes such as hexadecyltrimethoxysilane as an anti-pre-crosslinking agent. However, the mechanism of action of such traditional anti-scorching agents is the irreversible consumption of free radicals in the system, which leads to a waste of a large number of effective free radicals, thereby reducing the crosslinking density of the final product. To compensate for the loss of crosslinking degree, the amount of peroxide often needs to be increased during production, but this further exacerbates the generation of off-odor byproducts. In addition, Chinese patent application CN110016170A, published on July 16, 2019, discloses a polyolefin film containing isocyanate group-modified resin, but its technical purpose is to increase the crosslinking density by reacting with the surfactant to reduce water vapor permeability. It does not involve the chemical fixation of alcohol odor molecules produced by the decomposition of peroxides, nor does it address the issue of odor recovery.

[0006] Therefore, how to solve the problem of odor recovery in cross-linked polyolefin products, while taking into account the safety of compounding and the high cross-linking density of the final product, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0007] In view of the shortcomings of the prior art, the purpose of this invention is to provide a low-odor crosslinking masterbatch for polyolefins, which can effectively improve the odor recovery problem caused by conventional physical adsorption, alleviate the contradiction between processing safety and crosslinking efficiency, and improve the safety and dispersibility of additives in industrial production.

[0008] Another objective of this invention is to provide a method for preparing a low-odor crosslinking masterbatch for polyolefins. The method uses a low-temperature extrusion process to ensure the stability and controllability of the masterbatch preparation process. The resulting masterbatch exhibits excellent compatibility and dispersion uniformity in downstream application systems, which helps to improve the quality stability of the final product.

[0009] A third objective of this invention is to provide an application of a low-odor crosslinking masterbatch for polyolefins for the preparation of low-odor polyolefin crosslinked foam materials.

[0010] This invention is achieved using the following technical solution: The low-odor crosslinking masterbatch for polyolefins comprises, by weight: carrier resin: 30-50 parts; organic peroxide crosslinking agent: 20-40 parts; multifunctional crosslinking agent: 10-20 parts; temperature-responsive scorch inhibitor: 0.1-2.0 parts; covalent odor-locking powder: 10-20 parts; wherein the temperature-responsive scorch inhibitor is a nitrogen oxide free radical compound; and the covalent odor-locking powder is an inorganic silica powder with active isocyanate groups grafted onto its surface.

[0011] It should be noted that the "reversibility" mentioned in this invention refers to the following: under lower temperature conditions (e.g., ≤110℃), nitroxide radicals can capture trace amounts of carbon center radicals in the system, forming relatively stable dormant alkoxyamine species (CON bonds); under subsequent higher temperature conditions (e.g., ≥160℃), these dormant species undergo thermally induced homolytic cleavage, partially dissociating and releasing free radicals to participate in the crosslinking reaction. During this process, the dissociation efficiency is affected by factors such as temperature, system medium, and local concentration of free radicals; not all dormant species can dissociate. Compared with traditional irreversible free radical quenchers (such as hindered phenolic antioxidants), the use of nitroxide radical compounds has a relatively smaller negative impact on the final crosslinking density at the same addition amount, thus achieving a better balance between processing safety and crosslinking efficiency.

[0012] The carrier resin provides the basic matrix for the entire system, encapsulating each functional component to form macroscopically uniform particles. The organic peroxide crosslinking agent serves as the primary free radical donor. Multifunctional co-crosslinking agents, by providing active double bonds, assist free radicals in rapidly constructing a three-dimensional crosslinking network, helping to maintain the required crosslinking density with relatively low peroxide dosage. Nitrogen oxide free radical compounds (such as 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxy) can capture trace carbon-center free radicals in the system at a relatively high rate at lower temperatures (≤110℃), forming relatively stable alkoxyamine dormant species (CON bonds). During the subsequent high-temperature vulcanization stage (≥160℃), these dormant species undergo thermally induced homolytic cleavage, partially dissociating and releasing free radicals to participate in the crosslinking reaction. It should be noted that the dissociation efficiency of dormant species is affected by factors such as temperature, system medium, and local concentration of free radicals; not all dormant species can dissociate. Compared with traditional irreversible free radical quenchers (such as hindered phenolic antioxidants), within the addition range specified in this invention, nitrile radical compounds have a relatively small negative impact on the final crosslinking density, which helps to achieve a better balance between processing safety and crosslinking efficiency. It should be noted that the dissociation of dormant species at high temperatures is a thermodynamic equilibrium process, and the dissociation efficiency is affected by factors such as temperature, system viscosity, and local concentration of free radicals. Not all dormant species can dissociate and re-initiate crosslinking. However, experimental data show that under typical vulcanization conditions (165-175℃), the system using this scheme can still obtain a gel content of not less than 88% (see Table 2), which meets the requirements of industrial applications. The inorganic silicon oxide powder with surface rich in isocyanate groups undergoes a nucleophilic addition reaction with the alcohol byproducts produced by the decomposition of peroxides under high temperature conditions, utilizing the high reactivity of the isocyanate groups, and converts them into chemically stable urethane structures.

[0013] Preferably, the crosslinking masterbatch may contain the following components by weight: 40 parts carrier resin, 30 parts organic peroxide crosslinking agent, 15 parts multifunctional crosslinking agent, 0.5 parts temperature-responsive anti-scorching agent, and 14.5 parts covalent flavor-locking powder.

[0014] Furthermore, the carrier resin is generally selected from ethylene-vinyl acetate copolymers with a melt flow rate of 300-500 g / 10 min. This high-flow-rate resin facilitates rapid melting and wetting of the powder during masterbatch processing, reducing shear heating. The organic peroxide crosslinking agent can be selected from at least one of bis(tert-butylperoxyisopropyl)benzene or dicumyl peroxide; the multifunctional co-crosslinking agent can be selected from at least one of trimethylolpropane trimethacrylate and triallyl isocyanurate; the temperature-responsive scorch inhibitor is preferably 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxy(4-OH-TEMPO).

[0015] In another embodiment, the covalently flavor-locking powder is specifically a modified product obtained by a dealcoholization condensation reaction between 3-isocyanate-propyltriethoxysilane and silanol groups on the surface of fumed silica.

[0016] Typically, the crosslinking masterbatch exhibits excellent macroscopic testing performance. For example, when added to a conventional ethylene-vinyl acetate copolymer base at a dosage of 4.5 wt%, the Mooney scorch time (T10) at 110°C can be greater than 20 minutes; simultaneously, the crosslinked foam material prepared using this masterbatch can achieve a VDA270 odor rating of 2.0 or lower after baking at 80°C for 2 hours.

[0017] A method for preparing the above-mentioned low-odor crosslinking masterbatch for polyolefins is also provided, which mainly includes the following steps: Step 1, preparation of covalently flavor-locking powder: Inorganic silica powder that has undergone vacuum dehydration treatment (e.g., vacuum baking at 110-130℃) is dispersed in an organic solvent, and isocyanate-based silane coupling agent (usually accounting for 15%-25% of the powder weight) and catalyst are added. The mixture is heated and refluxed at a certain temperature (e.g., 80-95℃) for several hours (e.g., 3-5 hours). After purification and vacuum drying, covalently flavor-locking powder with isocyanate groups grafted on its surface is obtained. The second step is mixing and extrusion granulation: The aforementioned organic peroxide crosslinking agent, temperature-responsive anti-scorching agent, and the covalent flavor-locking powder obtained in the first step are mixed evenly to obtain a mixed powder. Subsequently, the carrier resin, the mixed powder, and the multifunctional crosslinking aid are fed into a twin-screw extruder. Melt blending and extrusion are performed under conditions where the temperature of each section of the extruder is controlled at 75℃-105℃ (feeding section 75-85℃, melting section 85-95℃, mixing section and die head 95-105℃). Finally, the crosslinked masterbatch is obtained by pelletizing (preferably underwater pelletizing). The extrusion temperature here is usually strictly controlled below the 1-hour half-life temperature of the organic peroxide crosslinking agent used. For example, the 1-hour half-life temperature of BIPB is approximately 135℃, and the maximum temperature in this process is 105℃, which is lower than this value, to ensure the safety of the production process. It should be noted that the extrusion temperature must be controlled below the 1-hour half-life temperature of the organic peroxide crosslinking agent to ensure safety during processing; at the same time, it must be ensured that the selected carrier resin can be fully plasticized within this temperature range. Testing has shown that the high melt flow rate EVA resin (MFI 300-500 g / 10 min) selected in this application can reach an effective melting state above 85°C.

[0018] Because the isocyanate groups grafted onto the powder surface are sensitive to moisture, they may hydrolyze in humid environments, generating amines and releasing carbon dioxide, thus reducing the flavor-locking function. Therefore, the following moisture-proof measures must be taken during the preparation, storage, and use of the masterbatch: All polymer base materials and unmodified functional additives should be dried in an 80℃ vacuum drying oven for 2-4 hours before use, until the moisture content is below 0.05% (mass fraction). The extrusion granulation process should be carried out in a dry atmosphere (ambient dew point ≤ -30℃), or nitrogen protection can be used. The finished masterbatch should be sealed in aluminum foil moisture-proof bags and stored in a dry, cool environment (temperature ≤ 30℃, relative humidity ≤ 40%). Under the above storage conditions, the half-life of the -NCO groups in the masterbatch is approximately 6 months (based on a -NCO content retention rate ≥ 80%), and it is recommended to use it within 4 months.

[0019] Preferably, the application of the aforementioned low-odor crosslinking masterbatch for polyolefins in the preparation of low-odor polyolefin crosslinked foam materials is also provided. During the high-temperature vulcanization molding stage at 165℃-175℃, the isocyanate groups (-NCO) on the surface of the covalently odor-locking powder can undergo nucleophilic addition reactions with alcohol byproducts containing active hydrogen (such as dimethylbenzyl alcohol, tert-butanol, etc.) generated from the thermal decomposition of organic peroxides, producing urethane structures. This reaction transforms some volatile small molecules into macromolecular networks or chemical anchoring sites on the surface of inorganic powders. Compared to physical adsorption, this covalent bonding method is expected to have better resistance to desorption under normal long-term use or thermal aging conditions. It should be noted that the reaction efficiency of the -NCO groups is affected by the moisture content of the system, the viscosity of the polymer melt, and the diffusion rate of byproducts; under typical vulcanization conditions (165-175℃, 15-20 min), according to liquid phase simulation experiments, the -NCO conversion rate can reach approximately 90% or more (see verification experiment C), but the conversion rate in actual polymer melts may be slightly lower. Furthermore, the -NCO group has no direct chemical bonding effect on ketone byproducts (such as acetophenone) that do not contain active hydrogen. The reduction of this type of odor mainly depends on the physical adsorption of the powder and the spatial binding effect of the cross-linked network.

[0020] Temperature-responsive scorch inhibitors (reversible equilibrium scorch inhibitors) refer to agents where, at lower temperatures (e.g., ≤110℃), nitroxide radicals capture trace carbon center radicals in the system, forming relatively stable dormant alkoxyamine species (CON bonds). At subsequent higher temperatures (e.g., ≥160℃), these dormant species undergo thermally induced homolytic cleavage, partially dissociating and releasing free radicals to participate in the crosslinking reaction. It should be noted that the dissociation efficiency is affected by factors such as temperature, system medium, and local concentration of free radicals; not all dormant species dissociate. Therefore, this process exhibits a temperature-dependent reversible equilibrium rather than complete reversibility. Compared to traditional irreversible free radical quenchers (such as hindered phenolic antioxidants), using nitroxide radical compounds has a relatively smaller negative impact on the final crosslinking density at the same addition amount, thus achieving a better balance between processing safety and crosslinking efficiency.

[0021] Covalent odor-locking powder: This refers to silicon oxide powder grafted with isocyanate-based silane coupling agents, whose surface contains reactive isocyanate groups (-NCO). During the high-temperature vulcanization stage, these groups can undergo nucleophilic addition reactions with byproducts containing active hydrogen produced by peroxide decomposition (such as alcohols like dimethylbenzyl alcohol), generating relatively stable carbamate structures. This reaction transforms some volatile small molecules into chemical anchoring sites on the surface of polymer networks or inorganic powders. Compared to traditional physical adsorption, covalent bonding is expected to have advantages in resistance to desorption under long-term use or thermal aging conditions. It should be noted that this powder does not have a direct chemical bonding effect on ketone byproducts without active hydrogen (such as acetophenone); the reduction of such odors mainly depends on the physical adsorption effect of the powder and the spatial binding effect of the cross-linked network. In addition, the -NCO groups are sensitive to moisture and may undergo hydrolysis side reactions in humid environments. Therefore, appropriate moisture-proof measures are recommended during masterbatch preparation, storage, and use.

[0022] It is important to note that the -NCO group is only reactive with compounds containing active hydrogen. The -NCO group cannot covalently bond with ketone byproducts produced by the decomposition of organic peroxides. The reduction of odor in these cases primarily relies on the physical adsorption effect of the powder and the steric entrapment effect of the cross-linked network. Therefore, in applications with extremely stringent odor requirements, it is recommended to prioritize peroxides whose decomposition byproducts are mainly alcohols, or to use ketone adsorbents in conjunction.

[0023] It should be noted that the reaction efficiency of the -NCO group with alcohol byproducts is affected by the moisture content of the system, the viscosity of the polymer melt, and the diffusion rate of the byproducts. In liquid-phase simulation experiments (165℃, no polymer medium), the -NCO conversion rate can reach approximately 96% within 15 minutes; however, in actual polymer melts (such as EPDM, 170℃, shear rate approximately 10 s⁻¹), the conversion rate is significantly lower. -1Due to diffusion limitations, the conversion rate of -NCO within the same time period is typically 78% to 85%. Therefore, in actual products, the anchoring efficiency of -NCO for alcohol odor molecules is between the two mentioned above. Combined with the physical adsorption effect of the powder itself, the VDA270 odor level of most products can still be controlled at level 2.0 or lower.

[0024] The conventional use conditions described in this invention refer to the typical operating conditions of polyolefin cross-linked foam products used long-term in indoor or vehicle interior environments, specifically including: maximum long-term operating temperature ≤80℃, relative humidity ≤75%, no direct ultraviolet radiation, and no contact with strong acid or alkali chemical media. Under these conditions, no significant increase in odor level was observed in the urethane covalent bonds during accelerated aging tests, indicating that it possesses acceptable thermal and hydrolytic stability under these conditions. It should be noted that this stability conclusion is based on laboratory accelerated aging tests, and long-term stability in actual use environments may be affected by a combination of factors.

[0025] The preferred TEMPO compounds of this invention serve as stable nitroxide radicals. During masterbatch extrusion (60-85°C) and subsequent low-mixing stages, their unpaired electrons move at a relatively high rate (k≈10). 8 The L / mol·s group captures trace carbon-centered free radicals generated by the decomposition of peroxides, forming dormant alkoxyamine species (CON bonds). During the vulcanization stage above 165℃, according to classical polymer thermodynamics, these alkoxyamine bonds undergo thermal decoupling and homolytic cleavage, releasing active free radicals, thus achieving a good processing safety period without sacrificing the final crosslinking density. The isocyanate (-NCO) on the surface of the covalently locked odor powder and the hydroxyl groups (-OH) in the peroxide byproducts undergo efficient nucleophilic addition in the polymer melt, generating urethane covalent bonds (-NH-CO-O-). These covalent bonds have high bond energy and are not easily broken, allowing odor molecules to become part of a large molecular network or inorganic powder. Compared to physical adsorption, this covalent bonding method improves desorption resistance under normal use conditions, helping to alleviate odor reactivation problems.

[0026] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention utilizes isocyanate groups grafted onto the surface of specific powders to undergo nucleophilic addition reactions with the hydroxyl groups of odor molecules during the high-temperature vulcanization stage, thereby constructing a relatively stable urethane covalent bond. Compared to the traditional physical adsorption mechanism, this covalent bonding method can still maintain an odor level below VDA2702.0 after 30 days of heat aging at 80℃ and ethanol extraction treatment, indicating that its anti-desorption ability under typical usage conditions is superior to physical adsorption.

[0027] (2) This invention introduces nitroxide free radical compounds as anti-scorching agents, which have a smaller negative impact on the final crosslinking density at the same addition amount compared with traditional irreversible free radical quenchers. Experimental data show that within the range of 0.1-2.0 parts of 4-OH-TEMPO addition, the gel content of the product can still reach more than 85%, meeting the requirements of industrial applications. The synergistic use of multifunctional crosslinking agents further helps to maintain the required mechanical properties under conditions of lower peroxide dosage.

[0028] (3) By selecting a carrier resin with high fluidity and preparing the above-mentioned active components into masterbatch, the risk of dust flying and frictional heating during the mixing of powder peroxides is reduced. The low-temperature extrusion process ensures the retention rate of active peroxides in the masterbatch preparation process. The masterbatch obtained has good dispersion uniformity in downstream application systems, which helps to improve the quality stability of the final product. Attached Figure Description

[0029] Figure 1 This is a schematic diagram of the "dormant-dissociation" equilibrium reaction mechanism of the temperature-responsive scorch inhibitor 4-OH-TEMPO in the low-temperature processing stage and the high-temperature vulcanization stage in the embodiments of this application.

[0030] Figure 2 This is a schematic diagram illustrating the principle of stable chemical bonding between the isocyanate groups grafted onto the surface of the covalently flavor-locking powder in the embodiments of this application and the peroxide decomposition byproducts (alcohols).

[0031] Figure 3 A bar chart showing the comparison of VDA270 odor level test results (before and after ethanol extraction) for samples prepared using the masterbatches of Example 1, Comparative Example 1, and Comparative Example 2. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it.

[0033] This invention provides a low-odor crosslinking masterbatch for polyolefins, its preparation method, and its application. By introducing covalently reactive odor-locking powders and temperature-responsive anti-scorching agents into the masterbatch, permanent chemical anchoring of odor molecules during polymer crosslinking and safe and controllable processing are achieved.

[0034] I. Formulation System: Carrier resin component: In some embodiments of the present invention, the carrier resin may be a polyolefin material with a high melt flow rate (MFI) to ensure rapid dispersion of the masterbatch. It may be selected from ethylene-vinyl acetate copolymer (EVA), polyethylene (PE), polyolefin elastomer (POE), or ethylene propylene diene monomer (EPDM). Preferably, the carrier resin is EVA with a VA content of 18%-40% and an MFI of 300-500 g / 10 min.

[0035] Organic peroxide crosslinking agent components: can be selected from bis(tert-butylperoxyisopropyl)benzene (BIPB), dicumyl peroxide (DCP), 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane (DHBP), etc.

[0036] Covalently locked flavor powder components: Powder matrix: can be an inorganic non-metallic powder with a large specific surface area, such as fumed silica, precipitated silica, alumina, titanium dioxide, porous aluminosilicate, or mesoporous molecular sieves. Preferably, the specific surface area is 150-300 m² / g. 2 / g of fumed silica.

[0037] Surface modifier: must contain isocyanate groups (-NCO), such as 3-isocyanate-propyltriethoxysilane, 3-isocyanate-propyltrimethoxysilane, etc.

[0038] Crosslinking agent components: can be selected from trimethylolpropane trimethacrylate (TMPTMA), triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), etc.

[0039] Temperature-responsive scorch inhibitor components: can be selected from compounds with stable nitrogen oxide free radicals, such as 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy (4-OH-TEMPO), 2,2,6,6-tetramethylpiperidine-1-oxy (TEMPO), or 4-oxo-TEMPO, etc.

[0040] For the reversible cyclic reaction mechanism of temperature-responsive scorch inhibitors, please refer to the appendix. Figure 1 As shown (at lower temperatures (≤110℃), nitroxide radicals capture carbon-center radicals to form dormant alkoxyamine species (CON bonds); at higher temperatures (≥160℃), some dormant species undergo thermally induced homolytic cleavage, releasing radicals to participate in the cross-linking reaction. It should be noted that this process is a thermodynamic equilibrium process, and the dissociation efficiency is affected by factors such as temperature, system medium, and local concentration of radicals; the equilibrium relationship is indicated by double-headed arrows in the figure). For the principle of stable chemical bonding between covalently flavor-locking powders and peroxide decomposition byproducts (alcohols), please refer to the appendix. Figure 2 As shown.

[0041] II. Raw material pretreatment and preparation methods: Powder dehydration pretreatment: To ensure that the isocyanate groups are not hydrolyzed, the powder matrix must undergo strict dehydration pretreatment before use. Treatment methods typically include: baking in a vacuum drying oven at 110℃-150℃ for 2-6 hours, or heating under an inert atmosphere to remove physically adsorbed water from the surface.

[0042] Covalent modification solvents and catalytic systems: When preparing covalently flavor-locking powders, the dispersion solvent used should be anhydrous, such as anhydrous toluene, anhydrous xylene, or n-hexane. Trace amounts of organotin compounds (such as dibutyltin dilaurate or stannous octoate) can be added as grafting catalysts. The reaction temperature is usually controlled at the solvent reflux temperature (80-110℃).

[0043] Extrusion granulation process: The method of applying the blended material to the extrusion equipment includes: premixing the powder using a high- and low-speed mixer, and then feeding it proportionally into a co-rotating twin-screw extruder or a reciprocating single-screw extruder using a loss-in-weight feeder. To prevent premature decomposition of peroxides, the temperature of each temperature zone of the extruder must be strictly controlled in a stepped gradient, with the highest temperature zone (mixing section and die head) strictly limited to the range of 60-85℃. Pelletizing can be done underwater or by air-cooled die-face hot cutting.

[0044] III. Application Methods: Applicable substrate types: The crosslinking masterbatch described in this invention can be widely used in the crosslinking or crosslinking foaming modification of various polyolefin substrates, such as EVA shoe material foaming, POE automotive interior foaming, PE crosslinked pipe (PEX), XLPE cable insulation, etc.

[0045] Pre-treatment and molding process: Before application to a specific product, a mixing process is usually required. This process may include: blending the base resin, foaming agent, functional filler, and crosslinking masterbatch of this invention in an internal mixer (90-110°C) or open mill. The final crosslinking, curing, and molding are then carried out using equipment such as a flatbed vulcanizing press (160-185°C), a continuous extruder, or a microwave hot air drying tunnel.

[0046] Raw material source and specifications: The specific sources and specifications of the main chemical reagents and materials used in all the following examples and comparative examples are shown in Table 1: Table 1: Sources and Specifications of Raw Materials for Examples and Comparative Examples

[0047] Specific examples of covalently flavor-locking powder preparation (the following examples and comparative examples all use this method): Fumed silica (specific surface area 200m²) 2The product (g) was dehydrated under vacuum at 110℃ for 4.0 hours. 100.0 g of the dehydrated powder was dispersed in 500 mL of anhydrous toluene, and a predetermined amount of 3-isocyanatopropyltriethoxysilane (IPTS) and 0.1 g of dibutyltin dilaurate (DBTDL) catalyst were added. Under a nitrogen atmosphere, the mixture was stirred at 300 rpm and refluxed at 80℃ for 3.0 hours. The product was separated by centrifugation and washed three times each with 200 mL of anhydrous toluene and anhydrous ethanol. Finally, it was dried in a vacuum drying oven at 60℃ and a vacuum degree of -0.09 MPa for 12.0 hours for later use.

[0048] The specific preparation ratios are as follows: Powder A: The mass of IPTS added is 15.0g.

[0049] Powder B: The mass of IPTS added is 18.0g.

[0050] Powder C: The mass of IPTS added is 25.0g.

[0051] Surface NCO content determination (di-n-butylamine back titration method): Accurately weigh 0.5 g of each powder sample (i.e., powder A, powder B, or powder C) and place them in a dry conical flask. Add 10 mL of 0.1 mol / L di-n-butylamine-toluene solution and shake for 30 minutes to allow the -NCO to react fully with the di-n-butylamine. Dilute with 20 mL of isopropanol and titrate with 0.1 mol / L HCl standard solution using bromocresol green as an indicator until the blue color turns yellow. Perform a blank control simultaneously.

[0052] -NCO content (mmol / g) = (V 空白 –V 试样 )×C HCl / m 试样 .

[0053] Measurement results: Powder B (grafting rate 18%): -NCO content 0.59mmol / g; Powder A (grafting rate 15%): -NCO content 0.49mmol / g; Powder C (grafting rate 25%): -NCO content 0.78mmol / g.

[0054] Grafting rate refers to the percentage of isocyanate-based silane coupling agent (IPTS) added during preparation to the mass of fumed silica, i.e., the number of grams of IPTS added to 100 g of silica. The actual surface-NCO content (mmol / g) is limited by the specific surface area of ​​silica and the density of surface silanol groups; the specific value is based on the measured value by di-n-butylamine back titration.

[0055] General preparation method for crosslinking masterbatch (used in the following examples and comparative examples): S1. Premixing: Weigh the carrier resin, organic peroxide, crosslinking agent, anti-scorching agent and covalent flavor-locking powder according to the formula, put them into a high-frequency mixer, mix for 5 minutes at an ambient temperature of 25°C at a set speed (500 rpm) to obtain a uniform premix.

[0056] S2. Melt Extrusion: The premixed material is fed into a co-rotating twin-screw extruder (L / D=40) for extrusion granulation. The screw speed is set to 150 rpm, the feeding rate is 5 kg / h, and the average residence time τ≈2.5 minutes. The crosslinked masterbatch is obtained by underwater pelleting and drying.

[0057] Example 1 Formula: EVA (brand name Evatane® 28-420, MFI=400): 40.0 kg, BIPB: 35.0 kg, TMPTMA: 15.0 kg, 4-OH-TEMPO: 1.0 kg, Powder A: 15.0 kg.

[0058] Extrusion temperature: The feeding section is set to 80℃, the melting section to 92℃, the mixing section to 102℃, and the die head to 102℃.

[0059] Example 2 Formula: Same as Example 1.

[0060] Extrusion temperature: The feeding section is set to 80℃, the melting section to 90℃, the mixing section to 100℃, and the die head to 100℃.

[0061] Example 3 Formula: Same as Example 1.

[0062] Extrusion temperature: The feeding section is set to 80℃, the melting section to 95℃, the mixing section to 105℃, and the die head to 105℃.

[0063] Example 4 Formulation: Same as in Example 1, except that 35.0 kg BIPB is replaced with an equal amount of dicumyl peroxide (DCP).

[0064] Extrusion temperature: Same as in Example 1.

[0065] Example 5 Formula: Same as in Example 1, except that powder A is replaced with 15.0 kg of powder B.

[0066] Extrusion temperature: Same as in Example 1.

[0067] Example 6 Formulation: Same as in Example 1, except that powder A is replaced with 15.0 kg of powder C.

[0068] Extrusion temperature: Same as in Example 1.

[0069] Example 7 Formulation: Same as Example 1, except that the carrier is replaced with 40.0 kg of Arkema Evatane® 18-500.

[0070] Extrusion temperature: Same as in Example 1.

[0071] Example 8 Formulation: Same as Example 1, except that the carrier is replaced with 40.0 kg of Arkema Evatane® 33-400.

[0072] Extrusion temperature: Same as in Example 1.

[0073] Example 9 Formula: EVA (MFI=400): 30.0kg, BIPB: 20.0kg, TMPTMA: 10.0kg, 4-OH-TEMPO: 0.1kg, Powder A: 10.0kg.

[0074] Extrusion temperature: Same as in Example 1.

[0075] Example 10 Formula: EVA (MFI=400): 50.0kg, BIPB: 40.0kg, TMPTMA: 20.0kg, 4-OH-TEMPO: 2.0kg, Powder A: 20.0kg.

[0076] Extrusion temperature: Same as in Example 1.

[0077] The comparative examples all used the same mixing time and screw speed as in Example 1.

[0078] Comparative Example 1: The formulation was the same as in Example 1, except that powder A was replaced with 15.0 kg of pure fumed silica without grafted silane. The extrusion temperature was the same as in Example 1.

[0079] Comparative Example 2: The formulation was the same as in Example 1, except that powder A was replaced with 15.0 kg of porous zeolite (5A molecular sieve). The extrusion temperature was the same as in Example 1.

[0080] Comparative Example 3: The formulation was the same as in Example 1, but 1.0 kg of 4-OH-TEMPO was completely removed. The extrusion temperature was the same as in Example 1.

[0081] Comparative Example 4: The formulation was the same as in Example 1, but 15.0 kg of TMPTMA was completely removed. The extrusion temperature was the same as in Example 1.

[0082] Comparative Example 5: The formulation was the same as in Example 1, but the amount of powder A added was forcibly increased to 35.0 kg. The extrusion temperature was the same as in Example 1. Observations during the extrusion granulation stage revealed that the melt flow rate decreased significantly. When using the same extrusion process parameters as in Example 1, the extruder torque increased, and obvious sharkskin phenomenon and periodic melt fracture appeared on the surface of the extruded sample. The granulated particles had irregular shapes. In the subsequent preparation of application samples, the masterbatch was difficult to disperse uniformly on the open mill, exhibiting obvious powder agglomeration. After vulcanization and tableting, a large number of undispersed particles were present on the surface of the sample, failing to meet the test standard requirements. Therefore, it was not included in the crosslinking degree and other test items. This result indicates that outside the powder addition range specified in this invention, when the addition amount is too high, the processing fluidity of the masterbatch may be significantly deteriorated, thereby affecting its dispersion effect in the substrate.

[0083] Comparative Example 6 Formulation: Same as in Example 1, except that 0.9 parts of 4-OH-TEMPO are replaced with an equal mass of hindered phenolic antioxidant Irganox 1010 (BASF).

[0084] Extrusion process: Same as in Example 1.

[0085] Application Sample Preparation and Testing The crosslinking masterbatches of Examples 1-10 and Comparative Examples 1-6 were added to EPDM rubber based on the effective peroxide content and the same activity level. The mixture was then mixed evenly on a two-roll mill at 90°C and vulcanized on a flat vulcanizing machine at 170°C and 15MPa for 15 minutes to prepare test samples.

[0086] To ensure the retention of the reactivity of the -NCO groups on the surface of the covalently flavor-locking powder during processing and to prevent urea bond hydrolysis side reactions with moisture in the air, the moisture content of the system is strictly controlled during the preparation and application of the masterbatch of this invention. All polymer base materials and unmodified functional additives must be dried in a vacuum drying oven at 80°C for 2-4 hours before use. The entire extrusion granulation process of the masterbatch must be carried out under a dry, slightly positive pressure nitrogen atmosphere with a dew point ≤ -40°C or in a closed system with highly efficient dry air.

[0087] Performance testing methods: The masterbatches prepared in the above embodiments and comparative examples were tested as follows: Extrusion process status: Observe whether the extruder's operating torque is stable and whether the particle surface is smooth.

[0088] Retention rate of active peroxides (iodometric titration): Accurately weigh 2.0 g of the masterbatch sample and dissolve it in 50 mL of a mixed solvent of glacial acetic acid and chloroform (volume ratio 2:1). Add 2 mL of saturated KI solution, react in the dark for 15 minutes, then add 50 mL of water. Titrate with 0.1 mol / L sodium thiosulfate standard solution, using starch solution as an indicator, until the blue color disappears as the endpoint. Perform a blank control and calculate the retention rate. When using the iodometric titration method, the endpoint is defined as the abrupt change of 0.5% starch solution from blue to colorless. Each sample should be measured in strict parallel triplicate, and the average value should be taken, ensuring that the relative deviation of the three measurements is less than 0.5%.

[0089] Mooney scorch time (T10): Using a Mooney viscometer with a large rotor (L), after 1 minute of preheating, the time (min) for the torque to rise 10 Mooney units from its lowest point at 110°C was measured. Because the decomposition kinetics of peroxides (such as BIPB) at 110°C are relatively slow, the 110°C static Mooney scorch (T10) test used in this specification is primarily based on the fundamental melt state of polymer rheology and serves only as a screening method for comparing the scorch prevention quality between different masterbatch formulations. In actual engineering scale-up evaluations, this test is further supplemented with dynamic rheometer crosslinking curves (MDR) at 130°C to evaluate the actual effect of the scorch prevention agent under shear-generating conditions.

[0090] Gel content (degree of crosslinking): Tested according to the xylene extraction method in ASTM D2765-16 standard "Determination of extractables in plastic products". The specific steps are as follows: Weigh approximately 0.5 g of sample (accurate to 0.0001 g), wrap it in a 120-mesh stainless steel mesh, and extract using a Soxhlet extractor with continuous reflux of xylene for 12 hours. After extraction, remove the sample, vacuum dry it at 80°C to constant weight, and weigh it. The gel content is calculated using the following formula: Gel content (%) = (dry weight of sample after extraction / net weight of sample before extraction) × 100%.

[0091] For samples containing inorganic fillers (such as silica), the gel content measurement may be overestimated because the fillers are insoluble in xylene. To correct this error, a blank sample (an equal volume of uncrosslinked mixture of the same formulation (without peroxide) extracted under the same conditions) was simultaneously measured to determine the residual filler content, which was then subtracted from the sample's dry weight after extraction. Each sample was measured in triplicate, and the average value was taken.

[0092] Odor rating test: Referencing VDA270:2019-06 standard "Determination of Odor Properties of Automotive Interior Materials". The vulcanized sample was cut into 50mm x 50mm pieces and placed in a pre-cleaned and dried 1L glass odor bottle. After sealing, it was heated in a constant temperature oven at 80℃±2℃ for 2 hours±10 minutes. After removal, it was cooled to 60℃±5℃, and five trained evaluators completed a blind olfaction assessment within 15 minutes. Evaluators scored independently, and the rating system adopted the VDA270 standard's 6-level scale. Level 1: Imperceptible; Level 2: Detectable, but not disruptive; Level 3: Clearly detectable, but not yet causing disturbance; Level 4: Interference; Level 5: Strong interference; Level 6: Intolerable.

[0093] The arithmetic mean of the scores from 5 evaluators is taken. If the difference between the highest and lowest scores exceeds two levels, the test is considered invalid and must be repeated. The environmental conditions for the odor test are: temperature 23℃±2℃, relative humidity 50%±5%.

[0094] Odor test after ethanol extraction: The sulfidated sample was continuously refluxed with anhydrous ethanol in a Soxhlet extractor for 24 hours. After extraction, it was vacuum dried at 60°C for 4 hours, and then the odor level was tested according to the above method. This test is used to evaluate the residue of odor substances after extraction with polar solvents, in order to distinguish the effects of covalent bonding and physical adsorption.

[0095] The test results of Examples 1-10 and Comparative Examples 1-6 are shown in Table 2.

[0096] Table 2: Test results of Examples 1-10 and Comparative Examples 1-6

[0097] Note: The retention rate of active peroxides was determined by iodometric titration. Each sample was measured three times in parallel, and the average value was taken. The measurement conditions were: room temperature 25℃±2℃, relative humidity 50%±10%. The relative deviation between the three measurements was less than 0.5%. It should be noted that the retention rate data are the results of laboratory-scale tests (feeding rate 5kg / h, screw speed 150rpm, average residence time approximately 2.5 minutes). In actual large-scale production, the retention rate may be slightly lower due to prolonged residence time and shear heat effect.

[0098] As shown in Table 2, when the extrusion temperature was adjusted within the range of 60-85℃ in Examples 1-3, the retention rate of active peroxide remained between 98.8% and 99.5%, the scorch T10 was stable at 27-28 minutes, the degree of crosslinking remained at 88.9%-89.2%, and the initial odor and the odor after ethanol reflux were both grade 1.0. These results indicate that within the extrusion temperature range of 60℃-85℃, small fluctuations in process parameters have no significant impact on the core performance of the masterbatch, and the low-temperature extrusion process has good window tolerance and production stability. In Example 4, after replacing BIPB with DCP, the retention rate of active peroxide, scorch T10, and degree of crosslinking were basically the same as in Example 1, but the initial odor increased to grade 1.5. This result indicates that BIPB, as a preferred peroxide, has advantages in odor control. Compared with Example 8, the scorch T10 in Example 7 and Example 8 were 27.1 min and 28.5 min, respectively, with no significant difference in the degree of crosslinking and odor grade. In Example 9, the scorch time T10 decreased to 21.2 min, and the crosslinking degree was 88.0%, slightly lower than in Example 1, but the odor grade of 1.5 was still acceptable. In Example 10, the scorch time T10 was extended to 30.5 min, the crosslinking degree was 89.5%, and the odor grade was 1.0.

[0099] The initial odor levels of Comparative Examples 1 and 2 were 4.5 and 2.5, respectively. After ethanol reflux, the odor levels remained at 4.5 and 4.5, respectively, a stark contrast to the 1.0 level of Example 1. This result directly demonstrates a serious odor recovery problem in the physical adsorption mechanism—although zeolite can reduce the odor in the initial stage through physical adsorption, it rebounds to level 4.5 after ethanol extraction and desorption; while the unmodified silica, lacking the -NCO active group, cannot covalently bond with alcohol byproducts, and its odor remains consistently at a high level of 4.5. The active peroxide retention rate of Comparative Example 3 plummeted to 85.2%, the scorch T10 was only 12.1 min, and the crosslinking degree dropped to 81.5%. This result indicates that without the protection of an anti-scorch agent, the shear heat during extrusion and mixing causes a large amount of peroxide to decompose prematurely, not only wasting raw materials but also severely damaging the crosslinking density of the final product. Although its odor level remained at 1.0, its overall performance no longer met the requirements, verifying the role of temperature-responsive anti-scorch agents in balancing processing safety and crosslinking efficiency. Comparative Example 4 showed normal retention of active peroxide and normal scorch T10, but its crosslinking degree was only 76.2%, resulting in poor tensile strength. This result indicates that, without a crosslinking aid, macromolecular free radical coupling induced solely by peroxides is insufficient to form a dense three-dimensional crosslinked network. Multifunctional crosslinking aids, by providing a high density of active double bonds, are essential components for ensuring the mechanical properties of the product. Comparative Example 5 showed a decrease in active peroxide retention to 96.5%, a scorch T10 to 25.1 min, and a sharp increase in apparent viscosity leading to melt fracture and inability to form sheets.

[0100] Verification Experiment A: Test method (Soxhlet extraction-titration): Take 10.0 g of powder A from the preparation example and place it in a Soxhlet extractor. Extract with anhydrous toluene under continuous reflux for 24 hours to remove unreacted IPTS that only undergo physical adsorption. After extraction, dry the powder in a vacuum drying oven (60 °C) to constant weight. The -NCO content of the extracted powder is determined by di-n-butylamine back titration.

[0101] As a control, a physically mixed powder was prepared: dehydrated fumed silica was mixed with an equal amount of IPTS at room temperature (without catalyst, without heating, and allowed to stand for 2 hours after mixing), and the initial -NCO content was tested under the same conditions and subjected to toluene extraction and titration.

[0102] Test results: Before extraction, the -NCO content of powder A was 0.49 mmol / g; after 24 hours of extraction, the -NCO content was measured to be 0.47 mmol / g (retention rate of approximately 95.9%).

[0103] The initial -NCO content of the control group (physically mixed powder) was 0.48 mmol / g; after extraction, the -NCO content decreased to 0.03 mmol / g.

[0104] The data above show that IPTS in powder A still maintains a high retention rate after toluene extraction, indicating that there is mainly a chemical bond between it and the powder surface; while the -NCO content of the physically mixed sample in the control group decreased significantly after solvent extraction, indicating that the physically adsorbed IPTS is easily removed under extraction conditions.

[0105] Verification Experiment B-1: Temperature-responsive rheological verification of the anti-scorching agent Test method: A rotorless vulcanizing apparatus (MDR) was used. The compounded rubber sheet used in Example 3 was selected as the experimental group, and the compounded rubber sheet used in Comparative Example 3 was selected as the control group.

[0106] Program settings: The first stage is maintained at a constant temperature of 110℃ for 30 minutes; then the temperature is increased to 170℃ within 1 minute and maintained for 20 minutes. The torque (S') change throughout the process is recorded.

[0107] Test results: Experimental group: Within 30 minutes at 110℃, the torque curve was stable (S' approximately 1.5 dN·m), with no obvious signs of crosslinking; after the temperature was raised to 170℃, the torque began to rise within 2 minutes, and the maximum torque (MH) reached approximately 18.2 dN·m.

[0108] Control group: When the temperature was kept constant at 110℃ for 12 minutes, the torque began to show an upward trend, and reached about 5.4 dN·m at 30 minutes; after the temperature was raised to 170℃, the torque continued to rise, and the maximum torque (MH) was about 13.5 dN·m.

[0109] The rheological data above indicate that the system containing the anti-scorching agent has a longer scorching lag period at 110℃, which is beneficial to processing safety; it also exhibits a higher final torque at 170℃, indicating that free radicals effectively participate in the crosslinking reaction at high temperatures. In contrast, the system without the anti-scorching agent shows a certain degree of pre-crosslinking at the 110℃ stage.

[0110] Verification Experiment B-2: Quantitative Assessment of the Influence of Anti-Scorching Agent on the Final Crosslinking Degree A comparative experiment was conducted: Under the same EPDM base material, the same BIPB dosage (3.0 parts of active ingredient), and the same vulcanization conditions (170℃×15min), 0, 0.5, 1.0, and 2.0 parts of 4-OH-TEMPO (introduced in masterbatch form) were added, respectively, and the gel content of each system was measured. The results are as follows: 0 portions: Gel content 92.1% 0.5 parts: Gel content 89.8% 1.0 part: Gel content 88.5% 2.0 portions: Gel content 85.2% The above data show that as the amount of anti-scorching agent increases, the degree of crosslinking shows a slight decreasing trend (approximately 3-4 percentage points decrease for every 1 part increase). However, within the dosage range (0.1-2.0 parts) specified in this invention, the degree of crosslinking remains at a level of not less than 85%, which is better than the control experiment of traditional hindered phenolic anti-scorching agents (gel content ≤80% at the same dosage).

[0111] Verification Experiment B-3: Comparison of Crosslinking Degree at Different Vulcanization Temperatures The EPDM compound containing the masterbatch from Example 1 was vulcanized at 130°C, 145°C, 160°C, and 175°C for the same time (20 min), and the gel content was measured. The results are as follows: 130℃: Gel content 18.5% (insufficient cross-linking, incomplete decomposition of peroxides) 145℃: Gel content 52.3% (partial cross-linking, incomplete dissociation of dormant species) 160℃: Gel content 81.2% (preliminary formation of cross-linked network) 175℃: Gel content 89.1% (fully cross-linked) This data indicates that the dormant 4-OH-TEMPO species can only effectively dissociate and release free radicals at temperatures above 160℃, verifying the temperature dependence of the reversible anti-scorching mechanism. Below 130℃, the system mainly exhibits free radical capture rather than release, thus ensuring processing safety.

[0112] Verification Experiment C-1: Test method: Take 5.0g of powder A and disperse it in 50mL of anhydrous xylene.

[0113] Two sets of experiments were conducted separately: Group 1: Add 1.0g of dimethyl benzyl alcohol (containing -OH); Group 2: Add 1.0g of acetophenone (without active hydrogen).

[0114] The mixture was stirred in a sealed container at 165°C for 15 minutes. The powder was then separated by centrifugation, washed three times with anhydrous xylene, and dried under vacuum. The mass change of the powder was weighed and recorded, and the remaining -NCO content was titrated.

[0115] Test results: Dimethylbenzyl alcohol group: The powder increased in mass by about 0.78g after washing and drying; titration showed that the -NCO content decreased from 0.49mmol / g to 0.03mmol / g.

[0116] Acetophenone group: The mass increase of the powder after washing and drying was less than 0.05 g; titration showed that the -NCO content was 0.48 mmol / g. The trace mass increase in the acetophenone group may be due to the physical adsorption of acetophenone by the powder pores or surface residue.

[0117] At 165℃, -NCO on the powder surface can react with alcohol molecules containing active hydrogen, resulting in a significant decrease in -NCO content and a significant increase in powder mass; however, it does not show a significant chemical binding effect on ketone molecules without active hydrogen.

[0118] Verification Experiment C-2: Simulation Evaluation of -NCO Conversion Efficiency in Polymer Melt Powder A, 5.0 g, was dispersed in EPDM melt (Keltan® 4450, 170℃ ± 2℃) and analyzed using a closed torque rheometer (Haake Polylab OS, rotor speed 60 rpm, corresponding to an average shear rate of approximately 10 s). -1Add 1.0 g of dimethylbenzyl alcohol, react for 15 minutes, dissolve the mixture in xylene, centrifuge to separate the powder, wash three times with anhydrous xylene, vacuum dry, and determine the remaining -NCO content using di-n-butylamine back titration. The results show that under these conditions, the -NCO conversion rate is approximately 78%–85% (average of three parallel experiments: 82%), lower than the 96% in the liquid-phase simulation system. This difference is due to the high viscosity of the polymer melt, which to some extent limits the diffusion rate of alcohol molecules to the powder surface. Nevertheless, in the actual vulcanization system, alcohol byproducts generated from peroxide decomposition still have the opportunity to contact the -NCO groups before the crosslinking network forms. Combined with the physical adsorption assistance of the powder itself, the masterbatch of this invention can control the odor level of the product to VDA2702.0 or below under most test conditions. It should be noted that these conversion rate values ​​are test results under laboratory conditions, and may vary in actual industrial production due to differences in process conditions.

[0119] Verification Experiment D: Masterbatch Processing Flowability Verification Test method: According to GB / T3682 standard, the melt flow rate (MFI, test conditions: 190℃, 2.16kg load) of the crosslinking masterbatch of Example 1 (15 parts of powder A added) and Comparative Example 5 (35 parts of powder A added) was determined, and the appearance of the extruded samples was observed.

[0120] Test results: The MFI of Example 1 was approximately 145 g / 10 min, and the surface of the extruded sample was smooth.

[0121] The MFI of Comparative Example 5 decreased to about 12 g / 10 min, the surface of the extruded sample was rough, and melt fracture occurred.

[0122] Within the powder addition range (10-20 parts) of the present invention, the masterbatch can maintain suitable melt flow properties, which is beneficial to the stability of the extrusion process; however, excessive powder addition (35 parts) will lead to a significant decrease in flowability and may affect the processing quality.

[0123] Verification Experiment E: Kinetic Simulation of the Reaction of -NCO with Small Molecules of Alcohols Test method: Using the liquid-phase simulation system of dimethylbenzyl alcohol in verification experiment C, samples were taken at 5, 10, 15, and 20 minutes of reaction under constant temperature of 165℃. The reaction was quickly quenched with a cold solvent, and after centrifugation and washing, the amount of unreacted -NCO residue was titrated. The conversion rate was calculated using the following formula: Conversion rate = (Initial - NCO content) (Post-reaction NCO content) / Initial NCO content × 100%.

[0124] Test results: After 5 minutes of reaction: the NCO conversion rate is approximately 55%. After 10 minutes of reaction: the NCO conversion rate is approximately 88%. Reaction time 15 minutes: - NCO conversion rate is approximately 96% (Note that in actual polymer melt systems, due to diffusion limitations, the conversion rate is typically 78%~85%, see verification experiment C-2 for details). Reacting for 20 minutes: -NCO conversion rate is approximately 98%.

[0125] Under the experimental conditions described above, most of the -NCO groups completed their reaction with the alcohol molecules within approximately 15 minutes. This reaction process is essentially consistent with the high-temperature vulcanization crosslinking cycle of conventional polyolefins (typically 15-20 minutes), indicating that under typical processing conditions, the -NCO groups have sufficient time to exert their covalent flavor-locking effect.

[0126] Application Example 1 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0127] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. According to iodometric titration (three parallel determinations, average value), the content of active BIPB in the masterbatch of Example 1 was approximately 32.5 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 99.2%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0128] Specific calculation: Masterbatch addition amount (parts) = target active BIPB content (3.0 parts) / active BIPB content in masterbatch (32.5%) = approximately 9.23 parts (actually 9.2 parts).

[0129] Mixing parameters: Internal mixer mixing, initial temperature 90℃, mixing time 8-10 minutes, discharge temperature ≤105℃.

[0130] Vulcanization parameters: flat vulcanizing machine, 170℃±2℃, pressure 15MPa, holding time 15 minutes±30 seconds.

[0131] Application Example 2 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0132] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 1.0 wt% of the weight of the substrate.

[0133] Specific calculation: Masterbatch addition amount (parts) = 1.0 part / 32.5% = approximately 3.08 parts (actually 3.1 parts).

[0134] Mixing parameters: Same as in Application Example 1.

[0135] Vulcanization parameters: Same as in Application Example 1.

[0136] Application Example 3 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0137] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 5.0 wt% of the weight of the substrate.

[0138] Specific calculation: Masterbatch addition amount (parts) = 5.0 parts / 32.5% = approximately 15.38 parts (actually 15.4 parts).

[0139] Mixing parameters: Same as in Application Example 1.

[0140] Vulcanization parameters: Same as in Application Example 1.

[0141] Application Example 4 Substrate: Polyolefin elastomer (POE, brand Engage® 8150, Dow Chemical): 100 parts (parts by weight, based on the weight of the substrate).

[0142] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the weight of the substrate.

[0143] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.5% = approximately 9.23 parts (actually 9.2 parts).

[0144] Mixing parameters: Internal mixer mixing, initial temperature 100℃, mixing time 8-10 minutes, discharge temperature ≤110℃.

[0145] Vulcanization parameters: flat vulcanizing machine, 165℃±2℃, pressure 15MPa, holding time 20 minutes±30 seconds.

[0146] Application Example 5 Substrate: Ethylene-vinyl acetate copolymer (EVA, VA content 18wt%, Yangzi Petrochemical-BASF Co., Ltd., MFI 500g / 10min): 100 parts (parts by weight, based on the weight of the substrate).

[0147] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. According to iodometric titration (three parallel determinations, average value), the content of active BIPB in the masterbatch of Example 1 was approximately 32.5 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 99.2%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0148] Specific calculation: Masterbatch addition amount (parts) = target active BIPB content (3.0 parts) / active BIPB content in masterbatch (32.5%) = approximately 9.23 parts (actually 9.2 parts).

[0149] Mixing parameters: Internal mixer mixing, initial temperature 85℃, mixing time 8-10 minutes, discharge temperature ≤100℃.

[0150] Vulcanization parameters: flat vulcanizing machine, 160℃±2℃, pressure 15MPa, holding time 25 minutes±30 seconds.

[0151] Application Example 6 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0152] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the weight of the substrate.

[0153] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.5% = approximately 9.23 parts (actually 9.2 parts).

[0154] Mixing parameters: Same as in Application Example 1.

[0155] Vulcanization parameters: flat vulcanizing machine, 180℃±2℃, pressure 15MPa, holding time 10 minutes±30 seconds.

[0156] Application Example 7 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0157] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was used. The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the weight of the substrate.

[0158] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.5% = approximately 9.23 parts (actually 9.2 parts).

[0159] Mixing parameters: Same as in Application Example 1.

[0160] Vulcanization parameters: flat vulcanizing machine, 160℃±2℃, pressure 15MPa, holding time 30 minutes±30 seconds.

[0161] Application Example 8 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0162] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 9 above was used. The content of active BIPB in the masterbatch of Example 9 was determined by iodometric titration to be approximately 28.4 wt% of the total masterbatch weight (theoretical value: 20 parts BIPB in the formulation of Example 9, total 70.1 parts, theoretical BIPB content 28.53 wt%, retention rate 99.4%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0163] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 28.4% = approximately 10.56 parts (actually 10.6 parts).

[0164] Mixing parameters: Same as in Application Example 1.

[0165] Vulcanization parameters: Same as in Application Example 1.

[0166] Application Example 9 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0167] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 10 was used. The content of active BIPB in the masterbatch of Example 10 was determined by iodometric titration to be approximately 29.8 wt% of the total masterbatch weight (theoretical value: 40 parts BIPB in the formulation of Example 10, total 132 parts, theoretical BIPB content 30.30 wt%, retention rate 98.5%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0168] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 29.8% = approximately 10.07 parts (actually 10.1 parts).

[0169] Mixing parameters: Same as in Application Example 1.

[0170] Vulcanization parameters: Same as in Application Example 1.

[0171] Application Example 10 The sample prepared in Application Example 1 was placed in an 80°C constant temperature oven for 7, 14, and 30 days of aging. At each time point, the odor level was tested according to VDA270:2019 standard (see the test method section of the instruction manual for details).

[0172] Results: Before aging: Grade 1.0; 7 days: Grade 1.0; 14 days: Grade 1.0; 30 days: Grade 1.0. This result indicates that under the experimental conditions, no increase in odor grade was observed in the samples treated with covalent bonding after long-term thermal aging.

[0173] Application Example 11 Substrate: Ethylene-vinyl acetate copolymer (EVA, VA content 28%, MFI 400 g / 10 min, Arkema Evatane® 28-420): 100 parts by weight.

[0174] Foaming agent: Azodicarbonamide (ADC, Jiangsu Suopu, foaming agent grade, decomposition temperature 200±5℃): 3.5 parts.

[0175] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above was added according to the weight of the substrate, so that the active BIPB content in the system was 3.0 wt% of the substrate (the amount of masterbatch added was about 9.2 parts).

[0176] Other additives: Zinc oxide (analytical grade, Sinopharm Group): 1.5 parts; stearic acid (industrial grade, Malaysian natural oils): 0.8 parts.

[0177] Mixing parameters: Internal mixer mixing, initial temperature 85℃, mixing time 10 minutes, discharge temperature ≤100℃.

[0178] Vulcanization / foaming parameters: flat vulcanizing machine, 165℃±2℃, pressure 15 MPa, holding time 20 minutes, foaming ratio approximately 1.8 times.

[0179] Test results: Gel content 86.5%, VDA270 odor rating initially 1.0, still 1.5 after 30 days of heat aging at 80℃, meeting the requirements for automotive interior foam materials.

[0180] Application Comparative Example 1 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0181] Crosslinking masterbatch: The masterbatch prepared using Comparative Example 1 described above. The content of active BIPB in the Comparative Example 1 masterbatch, determined by iodometric titration, was approximately 32.4 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 98.5%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0182] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.4% = approximately 9.26 parts (actually 9.3 parts).

[0183] Mixing parameters: Same as in Application Example 1.

[0184] Vulcanization parameters: Same as in Application Example 1.

[0185] Application Comparative Example 2 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0186] Crosslinking masterbatch: The masterbatch prepared using Comparative Example 2 described above. The content of active BIPB in the Comparative Example 2 masterbatch, determined by iodometric titration, was approximately 32.4 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 98.7%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0187] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.4% = approximately 9.26 parts (actually 9.3 parts).

[0188] Mixing parameters: Same as in Application Example 1.

[0189] Vulcanization parameters: Same as in Application Example 1.

[0190] Application Comparative Example 3 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0191] Crosslinking masterbatch: The masterbatch prepared using Comparative Example 3 described above. The content of active BIPB in the Comparative Example 3 masterbatch, determined by iodometric titration, was approximately 28.0 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 85.2%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0192] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 28.0% = approximately 10.71 parts (actually 10.7 parts).

[0193] Mixing parameters: Same as in Application Example 1.

[0194] Vulcanization parameters: Same as in Application Example 1.

[0195] Application Comparative Example 4 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0196] Crosslinking masterbatch: The masterbatch prepared using Comparative Example 4 described above. The content of active BIPB in the Comparative Example 4 masterbatch, determined by iodometric titration, was approximately 32.7 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 99.1%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0197] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.7% = approximately 9.17 parts (actually 9.2 parts).

[0198] Mixing parameters: Same as in Application Example 1.

[0199] Vulcanization parameters: Same as in Application Example 1.

[0200] Application Comparative Example 5 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0201] Crosslinking masterbatch: The crosslinking masterbatch prepared in Example 1 above. Calculated according to the method in Application Example 1, the amount of masterbatch added is approximately 9.2 parts, so that the theoretical content of active BIPB in the system is equivalent to 3.0 wt% of the substrate weight.

[0202] Mixing parameters: Same as in Application Example 1 (internal mixer mixing, initial temperature 90℃, mixing time 8-10 minutes, discharge temperature ≤105℃).

[0203] Vulcanization parameters (comparative settings): flat vulcanizing machine, 145℃±2℃, pressure 15MPa, holding time 15 minutes±30 seconds.

[0204] Application Comparative Example 6 Substrate: Ethylene propylene diene monomer (EPDM, grade Keltan® 4450, Arlanxynco): 100 parts by weight (based on the weight of the substrate).

[0205] Crosslinking masterbatch: The masterbatch prepared using Comparative Example 6 described above. The content of active BIPB in the Comparative Example 6 masterbatch, determined by iodometric titration, was approximately 32.4 wt% of the total masterbatch weight (theoretical value 35.0 wt% × retention rate 98.2%). The masterbatch was added based on the weight of the substrate, so that the content of active BIPB in the system was equivalent to 3.0 wt% of the substrate weight.

[0206] Specific calculation: Masterbatch addition amount (parts) = 3.0 parts / 32.4% = approximately 9.26 parts (actually 9.3 parts).

[0207] Mixing parameters: Same as in Application Example 1.

[0208] Vulcanization parameters: Same as in Application Example 1.

[0209] Testing standards: Degree of crosslinking: according to ASTM D2765 xylene reflux extraction method.

[0210] Tensile strength: Tested according to GB / T528 standard, tensile rate 500mm / min.

[0211] Odor rating (core indicator): Blind smell rating from 1 to 5; "Post-extraction odor" is re-rated after Soxhlet reflux of anhydrous ethanol for 24 hours.

[0212] The test results of Application Examples 1-9 and Application Comparative Examples 1-6 are shown in Table 3.

[0213] Table 3: Test results of application examples 1-9 and application comparative examples 1-6

[0214] Table 3 shows that Application Example 1 had a crosslinking degree of 89.2%, a tensile strength of 15.5 MPa, and an initial odor and an odor grade of 1.0 after ethanol reflux. This indicates that the masterbatch exhibits good compatibility and dispersion uniformity in downstream EPDM substrates. Application Example 2 had a crosslinking degree of 81.5% and a tensile strength of 12.0 MPa; while exhibiting excellent odor, its mechanical properties were relatively low. Application Example 3 had a crosslinking degree of 93.5% and a tensile strength of 16.8 MPa, with the odor grade rising to 1.5. This indicates that the amount of peroxide added is positively correlated with the crosslinking degree and mechanical properties, but negatively correlated with the odor level. Application Example 4 had a crosslinking degree of 88.6%, a tensile strength of 18.2 MPa, and an odor grade of 1.0; Application Example 5 had a crosslinking degree of 87.5%, a tensile strength of 14.5 MPa, and an odor grade of 1.0. This indicates that the masterbatch of this invention is suitable for various polyolefin substrates. In POE, it exhibits higher tensile strength due to the elastomer properties of the substrate itself, and in EVA, it exhibits good interfacial compatibility due to the presence of VA polar groups. Compared with Application Example 7, Application Example 6 showed no significant difference in crosslinking degree and tensile strength, and both had an odor grade of 1.0. This result indicates that the masterbatch of this invention can achieve effective crosslinking within the vulcanization temperature range of 160℃-180℃. Furthermore, the temperature-responsive anti-scorching agent fully dissociates and releases free radicals at 160℃, and the -NCO groups of the covalently locked odor powder can react efficiently with alcohol byproducts within the 160℃-180℃ range, indicating a wide process window. Application Example 8 showed a crosslinking degree of 88.0%, a tensile strength of 14.9 MPa, and an odor grade of 1.5; Application Example 9 showed a crosslinking degree of 89.5%, a tensile strength of 15.8 MPa, and an odor grade of 1.0. These results are consistent with the trend in Table 1. The lower limit masterbatch, due to its lower concentration of effective functional components, exhibits slightly inferior odor control compared to the upper limit masterbatch, but still meets the requirements for industrial applications. Application Example 10, after aging at 80℃ for 7, 14, and 30 days, consistently maintained an odor grade of 1.0, with no odor rebound. This result directly demonstrates the long-term stability of the covalent bonding mechanism—the urethane covalent bonds do not break or reverse under high-temperature aging conditions, resolving the odor recovery problem caused by easy desorption from physical adsorption. For a detailed comparison of odor test results (before and after ethanol extraction), especially the differences between physical adsorption and covalent odor-locking mechanisms, please refer to the appendix. Figure 3 The bar chart is shown below.

[0215] Comparative Example 1 initially had an odor grade of 4.5, which increased to 4.5 after ethanol reflux, with a crosslinking degree of 88.5% and a tensile strength of 15.1 MPa. This result indicates that without the -NCO covalent odor-locking function, even with normal crosslinking degree and mechanical properties, the odor problem cannot be solved, and there was no desorption rebound phenomenon in physical adsorption. Comparative Example 2 initially had an odor grade of 2.5, which surged to 4.5 after ethanol reflux, with a crosslinking degree of 88.0%. This result is consistent with the data for Comparative Example 2 in Table 1, forming a physical adsorption failure mode of "initial adsorption-extraction desorption". Comparative Example 3 had a large amount of deactivated masterbatch during preparation and application mixing, resulting in insufficient effective peroxides, a crosslinking degree of only 81.5%, and a low tensile strength of 11.2 MPa. Although the odor grade remained at 1.0, the mechanical properties did not meet the usage requirements. Comparative Example 4 had a crosslinking degree of only 76.2% and a poor tensile strength of 9.5 MPa. This result is consistent with Comparative Example 4 in Table 1, indicating that a dense cross-linked network cannot be constructed without a cross-linking agent in the application. Multifunctional cross-linking agents are essential for ensuring the mechanical properties of the product. Comparative Example 5 showed a cross-linking degree of only 18.5%, a tensile strength <5.0 MPa, and could not be tested for odor. This result indicates that 145℃ is below the dissociation critical temperature of the dormant alkoxyamine species. The temperature-responsive scorch inhibitor did not release effective free radicals, and the peroxide decomposition rate was low, resulting in the cross-linking reaction being almost impossible.

Claims

1. A low-odor crosslinking masterbatch for polyolefins, characterized in that, By weight, its components include: Carrier resin: 30-50 parts; Organic peroxide crosslinking agent: 20-40 parts; Multifunctional crosslinking agent: 10-20 parts; Temperature-responsive scorch inhibitor: 0.1-2.0 parts; Covalently locked odor powder: 10-20 parts; The covalently flavor-locking powder is an inorganic silica powder with active isocyanate groups grafted onto its surface; and the covalently flavor-locking powder is a modified product obtained by a de-alcoholization condensation reaction between 3-isocyanate-propyltriethoxysilane and silanol groups on the surface of fumed silica. The carrier resin is selected from ethylene-vinyl acetate copolymer with a melt flow rate of 300-500 g / 10 min; The organic peroxide crosslinking agent is selected from at least one of bis(tert-butylperoxyisopropyl)benzene or dicumyl peroxide; The multifunctional crosslinking agent is selected from at least one of trimethylolpropane trimethacrylate and triallyl isocyanurate; The temperature-responsive scorching inhibitor is 4-hydroxy-2,2,6,6-tetramethylpiperidine-1-oxy.

2. The low-odor crosslinking masterbatch for polyolefins according to claim 1, characterized in that, By weight, the crosslinking masterbatch comprises: 40 parts of carrier resin, 30 parts of organic peroxide crosslinking agent, 15 parts of multifunctional crosslinking agent, 0.5 parts of temperature-responsive anti-scorching agent, and 14.5 parts of covalently locked flavor powder.

3. A method for preparing a low-odor crosslinking masterbatch for polyolefins as described in claim 1 or 2, characterized in that, Includes the following steps: S1. Preparation of covalently flavor-locking powder: Disperse inorganic silica powder that has been vacuum dehydrated in an organic solvent, add isocyanate-based silane coupling agent and catalyst, heat and reflux for condensation reaction, and after purification and vacuum drying, obtain the covalently flavor-locking powder with isocyanate groups grafted on the surface. S2. Mixing and extrusion granulation: The organic peroxide crosslinking agent, temperature-responsive anti-scorching agent and covalent flavor-locking powder obtained in step S1 are mixed evenly to obtain a mixed powder. The carrier resin, the mixed powder and the multifunctional crosslinking agent are fed into a twin-screw extruder respectively. Melt blending and extrusion are carried out at an extrusion temperature of 75℃-105℃, and the crosslinking masterbatch is obtained by pelletizing.

4. The preparation method according to claim 3, characterized in that, In step S1, the dehydration treatment is performed under vacuum baking at 110-130℃; the reflux condensation reaction is performed at a temperature of 80-95℃ for 3-5 hours; and the amount of isocyanate-based silane coupling agent added is 15%-25% of the weight of the inorganic silica powder.

5. The preparation method according to claim 3, characterized in that, In step S2, the extrusion temperature is lower than the 1-hour half-life temperature of the organic peroxide crosslinking agent; the temperature profile of the twin-screw extruder is set as follows: 50-60℃ in the feeding section, 70-80℃ in the melting section, and 80-85℃ in both the mixing section and the die head; the pelleting process adopts underwater pelleting.

6. The application of a low-odor crosslinking masterbatch for polyolefins as described in claim 1 or 2, characterized in that, It is used in the preparation of low-odor polyolefin crosslinked foam materials.

7. The application according to claim 6, characterized in that, The application process includes a mixing and high-temperature vulcanization molding stage: The crosslinking masterbatch is added in the mixing section at a temperature below 110°C, and the temperature-responsive anti-scorching agent in the system is used to capture free radicals to prevent pre-crosslinking. During the high-temperature vulcanization molding stage at 165℃-175℃, the isocyanate groups on the surface of the covalently flavor-locking powder in the system undergo a nucleophilic addition reaction with the alcohol byproducts volatilized from the thermal decomposition of organic peroxides to form urethane covalent bonds.

Citation Information

Patent Citations

  • Low-smell TPV (thermoplastic vulcanizate) formed by secondary coating with ABS (acrylonitrile-butadiene-styrene) substrate and preparation method thereof

    CN103497429A

  • Anti-pre-crosslinking rapid-solidification low-smoke zero-halogen flame-retardant silane crosslinking nano-modified polyolefin composition

    CN105153621A

  • Polyolefin elastomer rubber film with low water vapor permeability and preparation method thereof,

    CN110016170A

  • Low-odor thermoplastic elastomer as well as preparation method and application thereof

    CN118085457A

  • Low-odor TPV and applications of the low-odor TPV in triangular groove sealing strips

    CN107383568A